Penerapan Manajemen Kinerja Islam Dalam Meningkatkan Kedisiplinan Kerja Karyawan PT Garda Utama Indokarya Palembang - Putri Riski Alam Tasti; Hidayat HT; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Application of Islamic Performance Management in Improving Work Discipline of PT Employees. Indokarya Palembang Main Guard”. The purpose of this research is to determine the application of Islamic performance management in improving the work discipline of PT employees. Indokarya Palembang Main Guard. The method used in this research is a qualitative research method with a descriptive approach that examines and explains the problem clearly. Data collection techniques include observation, documentation interviews, then data analysis consisting of data reduction, data presentation and drawing conclusions/verification. and disciplinary theory popularized by Malayu Hasibuan. The results of this research show that Islamic performance management aims to build performance in accordance with Islamic law, a job based on very strong sharia, and carrying out company management with good disciplinary rules as taught in Islam to become a good Muslim worker. PT. Garda Utama Indokarta hopes that employees can work wholeheartedly and diligently in carrying out worship, because work is also worship as Islam teaches its people to work diligently and seriously, solely hoping for Allah's approval. in accordance with the theory put forward by Malayu Hasibuan which states that discipline is a person's awareness and willingness to obey all applicable regulations and social norms, which consist of employee attendance every day, punctuality of working hours, employee relations or welfare, employee compliance with regulations. PT. Garda Utama Indokarya continues to improve discipline among its employees. Leaders provide motivational directions and guidance so that employees work in accordance with company regulations.